Предмет: Алгебра,
автор: MaryMirb
cos^2 t + 1 - sin^2 t
Ответы
Автор ответа:
1
Ответ:
cos2 t + 1 - sin2 t =
= cos2 t + sin2 a + cos2 t - sin2 t =
= 2cos2 t =
= cos 2a + 1.
2) cos2 t + 1 - sin2 t =
= (cos2 t - sin2 t) + 1=
= cos 2a + 1.
Ответ: cos 2a + 1.
Автор ответа:
0
Ответ: 2cos²t
Объяснение:
1- sin² t =cos² t⇒
cos² t + 1 - sin² t = cos² t +( 1 - sin² t) =cos² t +cos² t =2cos²t
Похожие вопросы
Предмет: Русский язык,
автор: mukhatarovaroza
Предмет: Русский язык,
автор: f23f23f
Предмет: Українська мова,
автор: funy15
Предмет: Литература,
автор: Аноним